Between the implemented and the attained curriculum: The case of strategies for solving linear equations. (2018) - Ozruso-Haggiag, Sevinc Gila; Tabach, Michal
Highlights: The study focus on solving linear equations. The same intended curriculum – the same textbook. Implemented curriculum as enacted by three teachers. Attained curriculum as reflected from students tests. Links between implemented and attained curriculum. Abstract: This study focuses on examining connections between implemented and attained curriculum, as reflected in equation-solving processes in seventh grade according to the new curriculum for teaching mathematics in middle school in Israel. Our focus is twofold: 1) the lessons enacted by teachers who base their lessons on a particular textbook in order to teach their students strategies for solving linear equations, and 2) the extent to which these strategies are reflected in student outcomes. Our findings showed that the implemented curriculum supersedes the intended one in terms of the attained curriculum. Yet we find little evidence of students using the special solving methods designed by their teachers.